Trends in Informal Payments by Patients in Europe: A Public Health Policy Approach - Horodnic, Adrian V. (Frontiers in Public Health, 2021)
Background: A new institutional approach towards informal payments in healthcare views informal payments as arising when there is a misalignment between patients` values/norms (informal institutions) and the formal rules (formal institutions). However, little knowledge is available on the effectiveness of this approach in tackling informal payments in healthcare. This study aims to fill this gap by evaluating the trends in the effect of institutional misalignment on informal payments made by patients. Methods: A quantitative study design with data extracted from the last three waves of special Eurobarometer surveys on corruption was used to model the propensity of European patients in 27 EU countries and the UK to make informal payments. Multilevel logistic regression analysis was employed in order to test the relationship between the formal-informal institution misalignment and the likelihood to make informal payments. Sensitivity analyses were also performed to test the robustness of the findings. Results: The finding is that there is a strong association between the formal-informal institution misalignment and the likelihood to make informal payments for public healthcare services. Similarly, social norms play a pivotal role. When patients perceive that informal practices are widespread in the public healthcare sector they are more likely to make informal payments themselves. Conclusion: The outcome is a call for complementing deterrence measures towards informal payments in healthcare with measures aiming to reduce the formal-informal institution misalignment and to change the social norms. This can be achieved by improving the structural conditions at country level and by changing patients` values/norms and beliefs.